2014
DOI: 10.1038/npp.2014.87
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Function in Cigarette Smokers: An [18F]-DOPA PET Study

Abstract: Tobacco addiction is a global public health problem. Addiction to tobacco is thought to involve the effects of nicotine on the dopaminergic system. Only one study has previously investigated dopamine synthesis capacity in cigarette smokers. This study, exclusively in male volunteers, reported increased dopamine synthesis capacity in heavy smokers compared with non-smokers. We sought to determine whether dopamine synthesis capacity was elevated in a larger sample of cigarette smokers that included females. Dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…First, being a smoker may interfere with memory consolidation or retrieval and/or related discrimination processes, possibly via nicotinergic or dopaminergic mechanisms (Fu et al, 2007;Kutlu and Gould, 2015;Subramaniyan and Dani, 2015). Although several studies found alterations of dopaminergic functioning in smokers (Bloomfield et al, 2014;Cosgrove et al, 2015;Rademacher et al, 2015), there is evidence that dopamine is involved in the consolidation of safety memories to inhibit the return of fear responses (Haaker et al, 2013(Haaker et al, , 2015a. Second, maintained smoking habits (Winkler et al, 2011) and a persistent conditioned fear response in safe contexts might be due to an common underling deficit in flexibly adjusting learned associations.…”
Section: Discussionmentioning
confidence: 99%
“…First, being a smoker may interfere with memory consolidation or retrieval and/or related discrimination processes, possibly via nicotinergic or dopaminergic mechanisms (Fu et al, 2007;Kutlu and Gould, 2015;Subramaniyan and Dani, 2015). Although several studies found alterations of dopaminergic functioning in smokers (Bloomfield et al, 2014;Cosgrove et al, 2015;Rademacher et al, 2015), there is evidence that dopamine is involved in the consolidation of safety memories to inhibit the return of fear responses (Haaker et al, 2013(Haaker et al, , 2015a. Second, maintained smoking habits (Winkler et al, 2011) and a persistent conditioned fear response in safe contexts might be due to an common underling deficit in flexibly adjusting learned associations.…”
Section: Discussionmentioning
confidence: 99%
“…PET imaging acquisition and analysis All participants received a PET scan to index dopamine synthesis capacity at baseline. Subjects were asked not to eat or drink (except water), and refrain from alcohol for 12 h prior to scan and not to smoke for 2 h prior to the scan [40]. Imaging data were obtained on a Siemens Biograph 6 HiRez PET scanner (Siemens, Erlangen, Germany) in three-dimensional mode.…”
Section: Clinical Measuresmentioning
confidence: 99%
“…PET image analysis was conducted as previously described (Bloomfield et al, 2014). Interframe correction for head movement during the scan was performed by denoising the nonattenuation-corrected dynamic images using a level 2, order 64 Battle-Lemarie wavelet filter.…”
Section: Image Analysismentioning
confidence: 99%